2016
DOI: 10.1093/asj/sjw108
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Methicillin-ResistantStaphylococcus aureus(MRSA) Carrier Status in Patients Undergoing Post-Mastectomy Breast Reconstruction

Abstract: 2 Risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…(iv) Post-operation, have postoperative antibiotics been prescribed? Although Hart et al [20] found a low incidence of MRSA colonization (<5%) postoperatively following BR, they pointed out an association between postoperative MRSA colonization and the delayed wound healing. This drawn association arose because MRSA carriers showed a higher incidence of major complications as postoperative SSI followed by delayed wound healing.…”
Section: Implant-associated Infectionsmentioning
confidence: 93%
See 2 more Smart Citations
“…(iv) Post-operation, have postoperative antibiotics been prescribed? Although Hart et al [20] found a low incidence of MRSA colonization (<5%) postoperatively following BR, they pointed out an association between postoperative MRSA colonization and the delayed wound healing. This drawn association arose because MRSA carriers showed a higher incidence of major complications as postoperative SSI followed by delayed wound healing.…”
Section: Implant-associated Infectionsmentioning
confidence: 93%
“…The human breast contains endogenous flora originated from the nipple ducts, similar to that of the healthy skin [3]. Staphylococcal skin flora are commensally resided and commonly cultured from surgical sites following breast reconstruction (BR) [20]. The patient's skin is the predominant source of infection at the time of surgery.…”
Section: Implant-associated Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ADM defines this border regardless of subpectoral or prepectoral implant placement, violation of the IMF is not a contraindication to proceeding with prepectoral breast reconstruction. mupirocin is recommended for decolonization (19). Hibiclens showers in all patients the night before surgery is also recommended.…”
Section: The Boundaries Of the Breastmentioning
confidence: 99%
“…Organisms most often involved in breast prosthesis infection are Staphylococci (68.2%), usually S. aureus or S. epidermidis [3]. These organisms belong to normal skin flora and can colonize mammary ducts [4][5][6][7][8]. After incision of the skin and transection of the mammary ducts, the breast pocket is rapidly colonised.…”
Section: Introductionmentioning
confidence: 99%